Turbo Pascal programming 101 - Calvert, Charles (Carmel, Indiana : Sams Publishing, 1993)
Provides step-by-step instructions on how to program in Turbo Pascal. Includes dozens of examples to show the reader how to utilize what is covered in text. Provides complete coverage on the art of debugging.
Classroom 1. Quick Start -- Classroom 2. Basics -- Classroom 3. Structure Programming -- Classroom 4. Arrays and Text Files -- Classroom 5. Records and Typed Files -- Classroom 6. The Modular Structure of Large Programs -- Classroom 7. Sets and Enumerated Types -- Classroom 8. Is My Computer Alive? -- Classroom 9. Introduction to Pointers -- Appendixes -- Index.
Includes bibliographical references and index.
Keywords: TURBO PASCAL (COMPUTER PROGRAM LANGUAGE)